2000
DOI: 10.1021/jp002984k
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Hydrogen Bond in AromaticN-Sulfinylamines with Ortho H Atoms

Abstract: Calculated geometries are presented for five aromatic N-sulfinylamines, RNSO. All carry at least one hydrogen atom on the aromatic ring ortho to the NSO substituent, and all show a preference for a planar isomer in which the substituent's oxygen atom is oriented toward an ortho hydrogen. All these isomers exhibit a shortening of the corresponding CH bond. Using the quantum theory of atoms in molecules (AIM), it can be shown that a CH···O bonding interaction exists that meets all the characteristics of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Interaction with one water molecule is the simplest model in the study of the hydrolysis of N-sulfinylaniline (1). Even though the formation of a prereaction complex usually precedes the reaction, we were only able to locate complex 2a with water situated on top of the S=O bond (Fig.…”
Section: Reaction Of N-sulfinylaniline With One Water Moleculementioning
confidence: 94%
See 1 more Smart Citation
“…Interaction with one water molecule is the simplest model in the study of the hydrolysis of N-sulfinylaniline (1). Even though the formation of a prereaction complex usually precedes the reaction, we were only able to locate complex 2a with water situated on top of the S=O bond (Fig.…”
Section: Reaction Of N-sulfinylaniline With One Water Moleculementioning
confidence: 94%
“…Our interest in the electronic and molecular structures of NSO species (1,2) is closely related to their reactivity. NSulfinylamines (R-N=S=O) were first prepared by Michaelis in 1890 (3) and their reaction with water was one of the first properties to be observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…From a simplistic model, a red shift would be the expected effect as far as the D-HÁ Á ÁA interaction increases the D-H bond length. Blue shift has been described in C-HÁ Á ÁO, C-HÁ Á Áp and N-HÁ Á ÁO systems [34][35][36]. The explanations advanced for the blue shift effect were reviewed by Alabugin et al [37].…”
Section: H-bonding Manifestation From Calculated Vibrational Spectramentioning
confidence: 99%
“…However, calculations reported for the parent sulfinylaniline 11 and some others substituted sulfinylanilines [3][4][5] demonstrate that only the syn form is observed in liquid phase. 7 The same was also evidenced now as a consequence of the orbital interaction of oxygen lone pairs towards the σ* (C6-H1) orbital in the syn form (these interactions are absent in the anti configuration). In order to describe the conformational properties of the o-fluorosulfinylaniline, the potential energy function for rotation around the N=S bond was determined by structure optimizations at fixed dihedral angles C-N=S=O in steps of 30°.…”
Section: Quantum Chemical Calculations Analysismentioning
confidence: 68%
“…It is known that the N=S bond is a four electron bond with the S atom as the positive and the N atom as the negative end of the dipole while the SO bond has been described as S + -O -. 7 By using 1 H and 17 O NMR spectroscopies, experimental evidence for this C-H⋅⋅⋅O interaction was put forward. 5 Glass et al confirmed that the -N=S=O group is electron withdrawing in p-disubstituted benzenes, withdrawing electrons from the benzene ring.…”
Section: Introductionmentioning
confidence: 99%